STUDI LITERATUR PENGARUH SELF ESTEEM, SELF EFFICACY DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (PERUSAHAAN - Azri Muzayyana; Moeheriono; Rini Fatmawati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2020)
The study aims to investigate the variables related to the research title, analysis, and the conclusion to be relevant with the research title. For the research method, the writer uses literature study. Thus, the findings are obtained through the analysis of previous research. Furthermore, the results indicate a positive effect between self esteem toward the employee performance (service company); and self efficacy toward the employee performance (service company). As the result, there is a significant positive effect between job satisfaction on the employee performance (service company).